2011
DOI: 10.1016/j.jvs.2011.03.255
|View full text |Cite
|
Sign up to set email alerts
|

Low rehospitalization rate for vascular surgery patients

Abstract: Relatively low 30-day rehospitalization was accomplished in vascular surgery patients at a single university hospital. Moreover, planned rehospitalizations accounted for approximately 25% of readmissions in vascular surgery patients. Strategies designed to reduce rehospitalization in diabetics may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 15 publications
8
69
0
1
Order By: Relevance
“…25 Jackson et al reported a lower 30-day readmission rate of 4.2% for patients undergoing CEA at a single university hospital institution. 5 The low readmission rate reported by Jackson et al most likely represents single-institutional bias, as our rates are similar to other large population database analyses. When using large population data sets, readmission for carotid interventions appears to be greater than expected.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…25 Jackson et al reported a lower 30-day readmission rate of 4.2% for patients undergoing CEA at a single university hospital institution. 5 The low readmission rate reported by Jackson et al most likely represents single-institutional bias, as our rates are similar to other large population database analyses. When using large population data sets, readmission for carotid interventions appears to be greater than expected.…”
Section: Resultssupporting
confidence: 88%
“…16 Moreover, in a single-institutional, retrospective study, Jackson et al identified advanced age and diabetes as a predictors of readmission, specifically for vascular procedures (P ¼ .39). 5 Strategies need to be implemented for reduction in health care costs in the future, with the current focus of CMS on readmission rates. This can prove to be difficult as the definition of readmission depends on certain circumstances.…”
Section: Resultsmentioning
confidence: 99%
“…Co-morbidities associated with re-admission and infection in bivariable analysis included a diagnosis of diabetes at the time of the index procedure. Previous investigations have supported this conclusion indirectly by demonstrating a direct association between insulindependent diabetes and a higher risk of 30-d re-admission [4,12,22]. Although the association between diabetes and re-admission is not surprising, it may well represent an association between poor glucose control and an overall higher risk of infection.…”
Section: Discussionmentioning
confidence: 92%
“…22 Patients were excluded if their index stay was designated as emergency or urgent, was 30 or more d in length, had both an endovascular and an open procedure performed, or had another admission within three h of admission or discharge. We also excluded patients who were less than 21 y of age.…”
Section: Study Populationmentioning
confidence: 99%
“…Owing to the retrospective nature of their study, Engelbert and colleagues 23 were unable to capture readmission to other institutions. Jackson and colleagues 24 retrospectively studied 30-day readmission rates among 799 live patients discharged from a university-affiliated hospital after vascular surgery. They reported a 30-day readmission rate of 11.9%; the most common cause for readmission was wound complication.…”
Section: Discussionmentioning
confidence: 99%